Identification of Cellular MicroRNA Coupling Strand Displacement Polymerization and Nicking‐Endonuclease‐Based Cleavage. Issue 12 (10th August 2015) - Miao, Peng; Tang, Yuguo; Zhang, Qi; Bo, Bing; Wang, Jue
Abstract: A target induced recycling amplification method for the detection of cellular microRNA is reported based on strand displacement polymerization and nicking endonuclease mediated cleavage. Moreover, by utilizing silver nanoparticle‐based solid‐state Ag/AgCl reaction, ultrahigh sensitivity is achieved with powerful discriminating towards the identification of target microRNA. The limit of detection is as low as 70 am . This method also allows the detection of cellular microRNA by lysing cells, thus making it a powerful tool for microRNA expression profiling and disease diagnosis. Abstract : A highly sensitive method to identify cellular microRNA has been developed by coupling strand displacement polymerization and nicking‐endonuclease‐based cleavage. This strategy consists of having a blocker/signal DNA hybrid on the electrode, target induced strand displacement amplification composed of a primer and polymerase, and nicking endonuclease to cleave the complete blocker/signal DNA hybrid.